We sell our time no more: workers' struggles against lean production in the British car industry - Stewart, Paul; Richardson, Mike; Danford, Andy; Murphy, Ken; Richardson, Tony; Wass, Victoria (London, 2009)
"This is the story of struggles against management regimes in the car industry in Britain from the period after the Second World War until the contemporary regime of lean production.